Analysis of pile subjected to torsion in multi‐layered soil. (27th August 2013) - Misra, A.; Saggu, Rajni; Basu, D.; Chakraborty, T.
Summary A new method of analysis of piles in multi‐layered elastic soil subjected to a torque at the head is developed. The differential equation governing the angle of twist in the pile is derived using the variational principles of mechanics. The method of initial parameters is used to obtain closed‐form solutions of the angle of twist and torque in the pile as a function of depth. The inputs required for the analysis are shear moduli of pile and soil, pile geometry and thickness of soil layers. Copyright © 2013 John Wiley & Sons, Ltd.